Evaluation of alternatives of cryptocurrency accounting - Subačienė, Rasa; Kurauskienė, Natalija (Buhalterinės apskaitos teorija ir praktika, 2020)
The emergence and popularity of the cryptocurrency has caused a great deal of controversy in the scientific community over market development opportunities, further use of virtual money, and its integration into traditional accounting systems. The global financial market creates many opportunities to use electronic and virtual money for various types of transactions, and the question of how to record cryptocurrency and related transactions in accounting remains relevant. The aim of the research is to evaluate the alternatives of cryptocurrency accounting. For the research methods of scientific literature analysis, comparison, interpretation, information systematization, generalization were used. Although various authors, national and international accounting standards regulators provide their insights and recommendations on cryptocurrency accounting, a unified system has not been formed yet. Currently are analysed such alternatives of cryptocurrency accounting as financial asset, intangible asset or inventory.